2016
DOI: 10.1002/jcph.750
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tiotropium in Reducing Exacerbations of Chronic Obstructive Pulmonary Disease When Combined With Long‐Acting β2‐Agonists and Inhaled Corticosteroids: The OUTPUL Study

Abstract: Combined inhaled therapy in chronic obstructive pulmonary disease (COPD) is commonly used, but its benefits remain controversial. We assessed the effect of tiotropium in reducing COPD exacerbations when combined with long‐acting β2 agonists (LABA) and/or inhaled corticosteroids (ICS). This new‐user cohort study is based on administrative data from 3 Italian regions. We identified adults hospitalized for COPD from 2006 to 2009 who were newly prescribed a fixed LABA/ICS combination (double therapy). We classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…In our meta‐analysis, there was no direct comparison between both dual therapies, though our subgroup analysis demonstrated a greater reduction of COPD exacerbations in patients using triple therapy vs LABA/LAMA (29%) than in triple therapy vs ICS/LABA (18%); however, the difference was not statistically significant between both groups ( P = 0.38) (Figure ). Conversely, Ferroni et al conducted the OUTPUL study, which suggested no significant difference in moderate‐to‐severe COPD exacerbations between triple and ICS/LABA in a large cohort study; however, the difference was more significant when sub‐cohort analysis was performed in patients who had moderate‐to‐severe COPD exacerbations in the past year . The OUTPUL study was neither randomized nor controlled, which increased the risk of bias and confounding variables that may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our meta‐analysis, there was no direct comparison between both dual therapies, though our subgroup analysis demonstrated a greater reduction of COPD exacerbations in patients using triple therapy vs LABA/LAMA (29%) than in triple therapy vs ICS/LABA (18%); however, the difference was not statistically significant between both groups ( P = 0.38) (Figure ). Conversely, Ferroni et al conducted the OUTPUL study, which suggested no significant difference in moderate‐to‐severe COPD exacerbations between triple and ICS/LABA in a large cohort study; however, the difference was more significant when sub‐cohort analysis was performed in patients who had moderate‐to‐severe COPD exacerbations in the past year . The OUTPUL study was neither randomized nor controlled, which increased the risk of bias and confounding variables that may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Ferroni et al conducted the OUTPUL study, which suggested no significant difference in moderate-tosevere COPD exacerbations between triple and ICS/LABA in a large cohort study; however, the difference was more significant when sub-cohort analysis was performed in patients who had moderate-to-severe COPD exacerbations in the past year. 24 The OUTPUL study was neither randomized nor controlled, which increased the risk of bias and confounding variables that may have affected the results. COPD) trial showed reduction of moderate-to-severe COPD exacerbations with triple therapy consisting of budesonide, glycopyrrolate and formoterol fumarate in comparison to LABA/LAMA (glycopyrrolate and formoterol fumarate), but not dual therapy ICS/LABA (budesonide and formoterol).…”
Section: Discussionmentioning
confidence: 99%
“… 5 Frequent acute exacerbations also play an important role in decreased lung function and thereby increase disease severity and mortality. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that patient characteristics may play an important role in therapeutic efficacy, including exacerbation history and eosinophils; two key characteristics that we could not include here, and the heterogeneity in the literature has likely contributed to the differences in advice from GOLD and NICE. Additionally, the OUTPUL 38 observational study found no difference in risk for exacerbation comparing triple therapy to LABA+ICS; however, when narrowed to a pool of frequent exacerbators, they saw a significantly reduced risk for moderate exacerbations in triple therapy patients.…”
Section: Patient Characteristicsmentioning
confidence: 99%